Case report: A novel third-generation anti-CD19/CD22 CAR T-cells combined with auto-HSCT for relapsed Burkitt lymphoma - Xiaodan Luo; Ao Chen; Le Qin; Robert Weinkove; Rong Zhao; Ting Ye; Sihui Chen; Jianli Tang; Jianbo Liu; Jiayu Huang; Boyun Shi; Danyun Yuan; et al. (Frontiers in Immunology)
This study explores a novel therapeutic strategy for relapsed/refractory (R/R) Burkitt lymphoma (BL) by integrating autologous hematopoietic stem cell transplantation (ASCT) with tandem anti-CD19/CD22 chimeric antigen receptor (CAR) T cell therapy. A 20-year-old Asian male with refractory BL, whose lymphoma had not responded to multiple chemoimmunotherapy regimens, received myeloablative ASCT followed three days later by infusion of a novel third-generation CAR T cells engineered with CD28 and CD3ζ signaling domains, along with a TLR2 costimulatory domain. This resulted in sustained complete remission at the 306-day follow-up, without experiencing any severe complications. This case suggests that combining myeloablative ASCT with tandem anti-CD19/CD22 CAR T cell therapy could be an effective approach for R/R BL, warranting further clinical validation.